Che Omar Bin Che Soh V PP revisited: The effect of British Rule to the meaning of ‘Islamic Law’ within the Constitutional context of Malaysia - Mokhtar, Khairil Azmin (2012)
A word may have many meanings. Usually when there is a dispute as regards to the meaning of a word we refer to an authoritative or established dictionary for its meaning. However if the dispute is serious the matter have to be brought before the court, and the court shall decide the meaning of the word. In Malaysia, ‘Islam’, ‘Islamic Law’ or ‘Syariah’ have meanings which are generally understood by the people. However what people generally do not realize is within the context of Malaysian’s constitution and legal system, ‘Islamic Law’ has been assigned certain meaning and a defined scope. This has been discussed by the court in a landmark case of Che Omar bin Che Soh. It is interesting to note that the court have to reject the true meaning of ‘Islam’ and come up with another meaning in order to make it suitable for Malaysia. One of the main reasons of this peculiar situation is the effect of British rule before the Independence which introduces secularism into the legal system. The paper will deliberate how British ruler change the landscape of local legal system from Syariah oriented to western oriented system which inevitably caused the marginalization of Islamic law in the country.